PsycEXTRA Dataset 2006
DOI: 10.1037/e654652010-001
|View full text |Cite
|
Sign up to set email alerts
|

Providing Child Care to Military Families: The Role of the Demand Formula in Defining Need and Informing Policy

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 2 publications
0
7
1
Order By: Relevance
“…In other words, being a dual-military spouse is advantageous to female officers for this career milestone. This finding is surprising given the level of attention that issues and challenges facing dual-military couples have received from the research and policy communities (L. Miller et al, 2011;Smith, 2010;Moini, Zellman, and Gates, 2006;Steinberg, Harris, and Scarville, 1993;Teplitzky, 1988). Our study does not imply that dual-military couples do not face challenges with such issues as colocation and finding adequate and dependable childcare, as past research has demonstrated.…”
Section: Marriage and Dependentscontrasting
confidence: 53%
See 2 more Smart Citations
“…In other words, being a dual-military spouse is advantageous to female officers for this career milestone. This finding is surprising given the level of attention that issues and challenges facing dual-military couples have received from the research and policy communities (L. Miller et al, 2011;Smith, 2010;Moini, Zellman, and Gates, 2006;Steinberg, Harris, and Scarville, 1993;Teplitzky, 1988). Our study does not imply that dual-military couples do not face challenges with such issues as colocation and finding adequate and dependable childcare, as past research has demonstrated.…”
Section: Marriage and Dependentscontrasting
confidence: 53%
“…Long (2010) found that deployments have a negative relationship with retention intentions, and the negative effect is larger for dualcareer members than for other groups. Moini, Zellman, and Gates (2006) found that dual-military parents were substantially more likely than single parents to state in a survey that they would consider leaving because of childcare concerns. Laura Miller et al (2011) found a similar result in the context of a survey they conducted of Air Force families.…”
Section: Past Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Military families with a civilian spouse are much more likely to use parental care, and are consequently less likely to use any formal child care option, including DoD-sponsored child care. Focus groups conducted as part of the survey project indicate that for many families, parental care is the most preferred type of child care (Moini, Zellman, and Gates, 2006). Most of these families (just under 70 percent) that use parental care have a civilian spouse who does not work outside the home.…”
Section: Discussionmentioning
confidence: 99%
“…The 2004 RAND child care survey by Moini, Zellman, and Gates (2006) asked military families whether child care issues had prevented a parent from reporting for military duty either following the birth of a child or after the most recent relocation. Such problems were an issue for over one-third (36 percent) of dual-military families and over 10 percent of single parents, but only for fewer than 1 percent of families with a civilian spouse.…”
Section: Readiness and Productivitymentioning
confidence: 99%